Biological Nanoparticles in Vaccine Development - Curley, Stephanie M.; Putnam, David (Frontiers in Bioengineering and Biotechnology, 2022)
Vaccines represent one of the most successful public health initiatives worldwide. However, despite the vast number of highly effective vaccines, some infectious diseases still do not have vaccines available. New technologies are needed to fully realize the potential of vaccine development for both emerging infectious diseases and diseases for which there are currently no vaccines available. As can be seen by the success of the COVID-19 mRNA vaccines, nanoscale platforms are promising delivery vectors for effective and safe vaccines. Synthetic nanoscale platforms, including liposomes and inorganic nanoparticles and microparticles, have many advantages in the vaccine market, but often require multiple doses and addition of artificial adjuvants, such as aluminum hydroxide. Biologically derived nanoparticles, on the other hand, contain native pathogen associated molecular patterns (PAMPs), which can reduce the need for artificial adjuvants. Biological nanoparticles can be engineered to have many additional useful properties, including biodegradability, biocompatibility, and are often able to self-assemble, thereby allowing simple scale-up from benchtop to large-scale manufacturing. This review summarizes the state of the art in biologically derived nanoparticles and their capabilities as novel vaccine platforms.